Tab encapsulation structure of an electric core and encapsulation method thereof
Patent Information
- Application Number
- CN202611137293.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-29
- Publication Date
- 2026-10-20
AI Technical Summary
解决现有软包电芯极耳胶在热封过程中易被压穿导致电解液泄漏或短路的问题
[0026]上述技术方案中的一个技术方案具有如下优点或有益效果,通过局部加厚设计,并结合多层复合结构设计,有效分散热封压力,增强极耳与铝塑膜的粘结强度,从而在保证电芯安全性的同时,通过优化结构和材料,进一步提高电芯的常温循环性能,延长电芯使用寿命。解决现有软包电芯极耳胶在热封过程中易被压穿导致电解液泄漏或短路的问题。
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention belongs to the field of lithium-ion battery manufacturing technology, and particularly relates to a battery cell tab packaging structure and packaging method. Background Technology
[0002] In the process of realizing this invention, the inventors discovered that the prior art has at least the following problems:
[0003] In the production process of pouch cells, the tab adhesive is a key component connecting the tabs to the aluminum-plastic film. Its main function is to achieve a reliable seal between the tabs and the aluminum-plastic film during heat sealing. Conventional tab adhesives mainly have the following problems:
[0004] Risk of heat seal breakage: Conventional tab adhesives are difficult to withstand stress concentration during high temperature and high pressure (180-200℃, 0.5-0.7MPa) heat sealing process, which can easily cause cracking or excessive melting, resulting in direct contact between the tab metal strip and the aluminum-plastic film, causing a short circuit in the battery cell.
[0005] Insufficient sealing: The tab adhesive of conventional thickness is prone to aging and delamination during long-term charge and discharge cycles, leading to electrolyte leakage. Especially after soaking in an 85°C high-temperature environment for 24 hours, the peel strength drops to below 1.2N / mm, which seriously affects the cell life.
[0006] Limited cycle performance: Insufficient uniformity of electrode adhesive thickness and bonding strength will exacerbate stress accumulation at the interface between the electrode and the active material, leading to the shedding of the active material. Under conventional processes, the cell's room temperature cycle life is only about 500 cycles, and the capacity retention rate is ≤80%.
[0007] While existing technologies offer some improvements, such as using multi-layered tab adhesives or redesigning hot-pressing molds, these methods suffer from high costs, poor effectiveness, or complex processes. For example, while redesigning the hot-pressing mold can improve pressure distribution, it cannot fundamentally solve the problem of pressure puncture caused by insufficient thickness. Therefore, a simple and effective method is urgently needed to address these issues.
[0008] CN217544868U-Soft Pack Battery Cell Tab and Packaging Structure discloses a soft pack battery cell tab and packaging structure. By setting protrusions on the tab body and cooperating with the aluminum-plastic film packaging bag to guide the hot melt adhesive molten during the hot pressing process, an extended sealing area is formed with the aluminum-plastic film packaging bag in the thickness direction of the battery cell, but this method still cannot solve the above-mentioned technical problems. Summary of the Invention
[0009] The technical problem this invention aims to solve is to provide a battery cell tab packaging structure and its packaging method. Through localized thickening design combined with a multi-layer composite structure design, the heat-sealing pressure is effectively dispersed, enhancing the adhesion strength between the tab and the aluminum-plastic film. This ensures battery cell safety while further improving the cell's room-temperature cycling performance and extending its service life through optimized structure and materials. It also solves the problem that existing soft-pack battery cell tab adhesives are easily punctured during heat sealing, leading to electrolyte leakage or short circuits.
[0010] To solve the above-mentioned technical problems, the technical solution adopted by the present invention is: a battery cell electrode packaging structure, having:
[0011] The tab adhesive consists of a polypropylene base layer, a polyurethane intermediate layer, and an adhesive layer arranged from top to bottom, forming a three-layer structure.
[0012] The electrode adhesive is applied to the battery cell body and the electrode tabs;
[0013] The thickness of the tab adhesive located at the tab welding end and heat-sealing edge is greater than the thickness of the tab adhesive at other locations.
[0014] The thickness of the adhesive on the welding end and heat-sealed edge of the electrode tab is 0.12 mm; the thickness of the adhesive on other locations is 0.08 mm.
[0015] The polypropylene base layer is a modified polypropylene with a thickness of 60μm and a melting point of 135-150℃.
[0016] The polyurethane intermediate layer is an elastic polyurethane with a thickness of 30 μm, a glass transition temperature of -40℃, and an elastic modulus ≥12 MPa.
[0017] The adhesive layer is a 30μm thick metalophilic adhesive layer made of maleic anhydride modified polypropylene. It forms a chemical bond with the tab metal strip through polar groups, and the adhesive strength is ≥4.5N / cm.
[0018] The width of the tab adhesive at the welding end of the tab is 5-8mm; the width of the tab adhesive at the heat-sealed edge is 3-5mm.
[0019] The packaging method for the above-mentioned tab packaging structure includes the following steps:
[0020] 1) Preparation of tab adhesive;
[0021] 2) Use tab adhesive to encapsulate the battery cell;
[0022] 3) Test the performance of the packaged battery cells.
[0023] Modified PP-60μm, PU-30μm, and PP-g-MAH-30μm were used to form a composite film through a three-layer co-extrusion casting process. The extrusion temperature was controlled at 230-250℃, the traction speed was 6-8m / min, and the thickness uniformity deviation was ≤±3%. The adhesive layer was subjected to corona treatment, and the surface tension of the tab metal strip was ≥42mN / m.
[0024] Tab pretreatment: The surface of the tab metal strip is plasma cleaned to remove the oxide layer, and the roughness is controlled at 0.8-1.6μm; Adhesive coating and heat sealing: A slit coater is used to coat the tab welding end and heat sealing edge with composite tab adhesive, with a coating width of 5-8mm and a thickness of 0.12mm; After coating, the tab and aluminum-plastic film are heat sealed at 180-190℃ and 0.5-0.6MPa for 3-5 seconds to form a sealing area with a width of 10-12mm.
[0025] Heat seal strength test: 180° peel test is performed, requiring peel force ≥3.8N / cm, and the failure mode is cohesive failure of the adhesive layer; Cycle life test: The packaged cell is charged and discharged at 0.5C at 25℃, and the cycle is terminated when the capacity drops to 80% of the initial capacity, requiring ≥800 cycles.
[0026] One of the above technical solutions has the following advantages or beneficial effects: by using a locally thickened design combined with a multi-layer composite structure design, the heat-sealing pressure is effectively dispersed, and the bonding strength between the tabs and the aluminum-plastic film is enhanced. This ensures the safety of the battery cell while further improving its room-temperature cycling performance and extending its service life through optimized structure and materials. It also solves the problem that the adhesive on the tabs of existing soft-pack battery cells is easily punctured during heat sealing, leading to electrolyte leakage or short circuits. Attached Figure Description
[0027] Figure 1 This is a schematic diagram of the electrode packaging structure of the battery cell provided in an embodiment of the present invention;
[0028] Figure 2 for Figure 1 A schematic diagram of the electrode packaging structure of a battery cell;
[0029] Figure 3 for Figure 1 A schematic diagram of the electrode packaging structure of a battery cell;
[0030] The markings in the above figures are: 1. Polypropylene base layer, 2. Polyurethane intermediate layer, 3. Adhesive layer, 4. Cell body, 5. Tab, 6. Welding end, 7. Heat-sealed edge. Detailed Implementation
[0031] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0032] Example 1
[0033] See Figures 1-3 A battery cell tab encapsulation structure comprises: a polypropylene base layer 1, a polyurethane intermediate layer 2, and an adhesive layer 3 arranged sequentially from top to bottom, forming a three-layer tab adhesive; the tab adhesive is applied to the battery cell body 4 and the tabs 5; the thickness of the tab adhesive located at the tab welding end 6 and the heat-sealing edge 7 is greater than the thickness of the tab adhesive at other locations. Through localized thickening design, combined with a multi-layer composite structure design, the heat-sealing pressure is effectively dispersed, and the bonding strength between the tabs and the aluminum-plastic film is enhanced. This ensures battery cell safety while further improving the battery cell's room-temperature cycling performance and extending its service life through optimized structure and materials. It solves the problem that existing soft-pack battery cell tab adhesives are easily punctured during heat sealing, leading to electrolyte leakage or short circuits.
[0034] The thickness of the adhesive on the tab welding end 6 and the heat-sealed edge 7 is 0.12mm; the thickness of the adhesive on other locations is 0.08mm. Through localized thickening and a multi-layer composite structure, the heat-sealing pressure is effectively dispersed, enhancing the adhesion strength between the tab and the aluminum-plastic film. This ensures cell safety while further improving the cell's room-temperature cycling performance and extending its lifespan through optimized structure and materials. It also solves the problem of existing soft-pack cell tab adhesives being easily punctured during heat sealing, leading to electrolyte leakage or short circuits.
[0035] The polypropylene base layer 1 is a 60μm thick modified polypropylene with a melting point of 135-150℃. It exhibits good heat-sealing compatibility with the PP layer of the aluminum-plastic film, providing basic insulation and corrosion resistance. The 60μm thickness ensures sufficient mechanical strength and insulation performance while avoiding inadequate heat sealing due to an excessively thick overall adhesive layer. This thickness effectively prevents electrolyte penetration and corrosion while allowing for thorough fusion bonding with the PP layer of the aluminum-plastic film during heat sealing. The melting point is controlled at 135-150℃, keeping it below the heat-sealing temperature. This ensures the surface of the base layer melts fully during heat sealing while maintaining its internal structural integrity, resulting in good adhesion to the aluminum-plastic film and preventing uneven thickness and insulation failure due to excessive melting. This effectively prevents electrolyte corrosion and electrochemical erosion, significantly improving the long-term reliability and safety of the battery cell.
[0036] The polyurethane interlayer 2 is a 30μm thick elastic polyurethane with a glass transition temperature of -40℃ and an elastic modulus ≥12MPa. It can absorb mechanical stress during charge-discharge cycles and suppress the propagation of interfacial cracks. The 30μm thickness provides sufficient elastic deformation capacity to absorb stress without compromising the overall structural dimensional stability and thermal conductivity due to excessive thickness, effectively buffering the deformation differences between the tabs and the aluminum-plastic film during charge-discharge. The glass transition temperature of -40℃ ensures that the interlayer remains in a highly elastic state within the normal operating temperature range of the battery cell (-20℃ to 60℃), maintaining good elasticity and flexibility and avoiding brittleness and stress concentration caused by glass transition at low temperatures. The ≥12MPa elastic modulus design allows the interlayer to possess sufficient supporting strength while maintaining good elasticity, preventing excessive plastic deformation under heat sealing pressure and resulting in uneven adhesive layer thickness. The interlayer can reduce interfacial stress during charge-discharge cycles by more than 40%, effectively suppressing the generation and propagation of interfacial cracks and ensuring the integrity of the encapsulation structure in extreme low-temperature environments.
[0037] Adhesive layer 3 is a 30μm thick metalophilic adhesive layer made of maleic anhydride-modified polypropylene. It forms chemical bonds with the tab metal strip through polar groups, achieving an adhesion strength ≥4.5N / cm, significantly improving interfacial stability. The 30μm thickness ensures sufficient material for the adhesive layer to form adequate chemical bonds and mechanical interlocking with the metal surface, while avoiding excessive thickness that could lead to decreased overall rigidity and excessive heat-sealing deformation. This thickness allows the adhesive to fully wet the microscopic uneven structure of the metal surface, forming a uniform and dense adhesive interface. Introducing maleic anhydride polar groups enhances the adhesion performance between polypropylene and the metal surface, enabling the originally inert PP material to form chemical bonds with the tab metal strip, solving the problem of insufficient adhesion between traditional tab adhesives and the metal interface. The adhesion strength ≥4.5N / cm ensures that the interfacial strength is higher than the cohesive strength of the adhesive layer itself, effectively preventing electrolyte leakage and cell failure due to interfacial peeling during charge-discharge cycles, significantly improving the high-temperature reliability of the cell.
[0038] The width of the adhesive layer on the tab welding end 6 is 5-8mm; the width of the adhesive layer on the heat-sealed edge 7 is 3-5mm. The key thickened areas include the tab welding end 6 (5-8mm wide) and the heat-sealed edge 7 (3-5mm wide). The thickened adhesive layer effectively disperses the pressure generated during heat sealing, increasing the puncture resistance from 2.5N to over 5.2N, thus avoiding the risk of pressure-break-through. The 5-8mm thickened width at the tab welding end is designed to cover the stress concentration zone between the tab and the internal electrode sheet of the battery cell. This area, due to the uneven metal surface caused by welding, is the most prone to pressure-break-through during heat sealing. The 3-5mm thickened width at the heat-sealed edge enhances the sealing performance at the aluminum-plastic film fold, forming an effective sealing barrier at the fold. Differentiated thickening designs are implemented for different regions to ensure the protection effect in critical areas while minimizing material usage and overall thickness increase; the puncture resistance of key thickened areas is increased from the conventional 2.5N to over 5.2N, achieving an optimal balance between safety and lightweight.
[0039] Synergistic heat-sealing parameters: Optimized heat-sealing process (temperature 180-190℃, pressure 0.5-0.6MPa, time 3-5 seconds) ensures a uniform melt transition zone between the thickened tab adhesive and the aluminum-plastic film, with thickness deviation controlled within ±5%, avoiding localized over-melting or incomplete sealing. The heat-sealing temperature is set at 180-190℃ to ensure the tab adhesive surface reaches a fully melted state, forming good molecular diffusion and interfusion with the PP layer of the aluminum-plastic film, while ensuring that the internal polyurethane intermediate layer and adhesive layer do not undergo thermal decomposition or performance degradation. This temperature range is slightly higher than the PP melting point but much lower than the PU decomposition temperature, ensuring that all layers are in optimal heat-sealing condition. The heat-sealing pressure is set at 0.5-0.6MPa, providing sufficient pressure to promote close contact and molecular diffusion between the molten adhesive layer and the aluminum-plastic film, while avoiding excessive pressure that could cause the adhesive layer to be over-compressed, thinned, or even punctured, maintaining a uniform thickness distribution after heat sealing. The heat-sealing time is set to 3-5 seconds to ensure that heat is fully transferred to the interior of the adhesive layer, so that the interfaces of each layer reach a molten and bonded state, while avoiding thermal degradation and material aging caused by excessive time. Through the synergistic optimization of temperature, pressure, and time, a uniform and dense molten transition zone is formed between the thickened tab adhesive and the aluminum-plastic film.
[0040] 1. Preventing heat seal breakage: The local thickening design significantly improves the compressive strength of the tab adhesive, enabling it to withstand greater heat sealing pressure, effectively preventing breakage during the heat sealing process, reducing the risk of electrolyte leakage and short circuit, and improving the safety of the battery cell.
[0041] 2. Improved room temperature cycling performance: Through optimized structure and materials, the adhesion to the tabs and aluminum-plastic film is enhanced, reducing detachment and deformation during cycling, thereby improving the room temperature cycling performance of the battery cell. Experimental data shows that after adopting the tab adhesive of this invention, the room temperature cycle life of the pouch cell increases from the conventional 500 cycles to 800 cycles, and the capacity retention rate increases from 80% to 90%.
[0042] 3. Reduced production costs: The localized thickening design of this invention does not require complex production processes and equipment; it can be achieved simply by modifying existing molds, resulting in limited cost increases. Simultaneously, it improves the yield rate of battery cells and reduces the scrap rate due to poor heat sealing, further lowering production costs.
[0043] By adopting the above solution, through localized thickening and a multi-layer composite structure design, the heat-sealing pressure is effectively dispersed, and the bonding strength between the tabs and the aluminum-plastic film is enhanced. This ensures cell safety while further improving the cell's room-temperature cycling performance and extending its lifespan through optimized structure and materials. It also solves the problem of existing soft-pack cell tab adhesives being easily punctured during heat sealing, leading to electrolyte leakage or short circuits.
[0044] Example 2
[0045] The packaging method for the above-mentioned tab packaging structure includes the following steps:
[0046] 1) Prepare tab adhesive; 2) Encapsulate the battery cell using tab adhesive; 3) Test the performance of the encapsulated battery cell.
[0047] Modified PP-60μm, PU-30μm, and PP-g-MAH-30μm were used to form a composite film through a three-layer co-extrusion casting process. The extrusion temperature was controlled at 230-250℃, the traction speed was 6-8m / min, and the thickness uniformity deviation was ≤±3%. The adhesive layer was subjected to corona treatment, and the surface tension of the tab metal strip was ≥42mN / m.
[0048] Tab pretreatment: The surface of the tab metal strip is plasma cleaned to remove the oxide layer, and the roughness is controlled at 0.8-1.6μm; Adhesive coating and heat sealing: A slit coater is used to coat the tab welding end and heat sealing edge with composite tab adhesive, with a coating width of 5-8mm and a thickness of 0.12mm; After coating, the tab and aluminum-plastic film are heat sealed at 180-190℃ and 0.5-0.6MPa for 3-5 seconds to form a sealing area with a width of 10-12mm.
[0049] Heat seal strength test: 180° peel test is performed, requiring peel force ≥3.8N / cm, and the failure mode is cohesive failure of the adhesive layer; Cycle life test: The packaged cell is charged and discharged at 0.5C at 25℃, and the cycle is terminated when the capacity drops to 80% of the initial capacity, requiring ≥800 cycles.
[0050] 1. Preventing heat seal breakage: The local thickening design significantly improves the compressive strength of the tab adhesive, enabling it to withstand greater heat sealing pressure, effectively preventing breakage during the heat sealing process, reducing the risk of electrolyte leakage and short circuit, and improving the safety of the battery cell.
[0051] 2. Improved room temperature cycling performance: Through optimized structure and materials, the adhesion to the tabs and aluminum-plastic film is enhanced, reducing detachment and deformation during cycling, thereby improving the room temperature cycling performance of the battery cell. Experimental data shows that after adopting the tab adhesive of this invention, the room temperature cycle life of the pouch cell increases from the conventional 500 cycles to 800 cycles, and the capacity retention rate increases from 80% to 90%.
[0052] 3. Reduced production costs: The localized thickening design of this invention does not require complex production processes and equipment; it can be achieved simply by modifying existing molds, resulting in limited cost increases. Simultaneously, it improves the yield rate of battery cells and reduces the scrap rate due to poor heat sealing, further lowering production costs.
[0053] By adopting the above solution, through localized thickening and a multi-layer composite structure design, the heat-sealing pressure is effectively dispersed, and the bonding strength between the tabs and the aluminum-plastic film is enhanced. This ensures cell safety while further improving the cell's room-temperature cycling performance and extending its lifespan through optimized structure and materials. It also solves the problem of existing soft-pack cell tab adhesives being easily punctured during heat sealing, leading to electrolyte leakage or short circuits.
[0054] Example 3
[0055] A battery cell tab packaging structure optimizes the mechanical properties and heat-sealing behavior of the tab adhesive through local thickness gradient design and multilayer composite structure:
[0056] 1. Thickness Gradient Distribution: The local thickness of the tab adhesive is increased to 0.12mm, with key thickening areas including the tab welding end (5-8mm wide) and the heat-sealed edge (3-5mm wide). The thickened adhesive layer effectively disperses the pressure generated during heat sealing, increasing the puncture resistance from 2.5N to over 5.2N and avoiding the risk of pressure puncture. Increasing the local thickness to 0.12mm strengthens the areas with the highest stress concentration during heat sealing, improving the adhesive layer's puncture resistance and compressive strength, and preventing the risk of heat seal pressure puncture. The 5-8mm thickening at the tab welding end completely covers the stress concentration zone in the tab welding area; the 3-5mm thickening at the heat-sealed edge enhances the sealing performance at the aluminum-plastic film fold, preventing seal failure due to bending stress. The thickened adhesive layer effectively disperses the pressure generated during heat sealing, increasing the puncture resistance by over 100%.
[0057] 2. Three-layer composite structure: Utilizing a three-layer structure consisting of a modified polypropylene base layer, an elastic polyurethane intermediate layer, and a metal-philic adhesive layer: Base layer: A 60μm thick modified polypropylene (PP) layer with a melting point controlled at 135-150℃, exhibiting good heat-sealing compatibility with the PP layer of the aluminum-plastic film, providing basic insulation and corrosion resistance. Intermediate layer: A 30μm thick elastic polyurethane (PU) layer with a glass transition temperature (Tg) of -40℃ and an elastic modulus ≥12MPa, capable of absorbing mechanical stress during charge-discharge cycles and inhibiting interfacial crack propagation. Adhesive layer: A 30μm thick metal-philic adhesive layer made of maleic anhydride-modified polypropylene, forming chemical bonds with the tab metal strips through polar groups, achieving an adhesive strength ≥4.5N / cm, significantly improving interfacial stability. The modified polypropylene base layer, 60μm thick and with a melting point of 135-150℃, ensures sufficient mechanical strength and insulation performance while allowing the surface to fully melt during heat sealing while maintaining internal structural integrity. This results in good adhesion to the aluminum-plastic film PP layer, while also providing basic insulation and corrosion protection. The elastic polyurethane interlayer, 30μm thick, with a Tg of -40℃ and an elastic modulus ≥12MPa, maintains high elasticity across the entire operating temperature range of the battery cell. This effectively absorbs mechanical stress during charge-discharge cycles, inhibits interfacial crack propagation, and provides sufficient support strength to prevent excessive deformation during heat sealing. The metalophilic adhesive layer, 30μm thick and made of maleic anhydride-modified polypropylene with an adhesive strength ≥4.5N / cm, forms chemical bonds with the tab metal strip through polar groups, fundamentally improving interfacial adhesion and ensuring that the interfacial strength is higher than the cohesive strength of the adhesive layer. The three-layer structure works synergistically to give the tab adhesive excellent insulation, elastic cushioning, and metal bonding performance. Compared with traditional single-layer tab adhesive, the heat sealing strength is increased by more than 50%, which comprehensively improves the reliability and service life of the battery cell packaging.
[0058] 3. Synergistic Heat Sealing Parameters: Optimized heat sealing processes (temperature 180-190℃, pressure 0.5-0.6MPa, time 3-5 seconds) ensure a uniform melt transition zone between the thickened tab adhesive and the aluminum-plastic film, with thickness deviation controlled within ±5%, preventing localized over-melting or incomplete sealing. The heat sealing temperature of 180-190℃ allows the polypropylene surface layer of the tab adhesive to fully melt and form molecular-level interfusion with the PP layer of the aluminum-plastic film, while ensuring that the internal polyurethane layer and adhesive layer do not undergo thermal degradation. The heat sealing pressure of 0.5-0.6MPa promotes close contact and molecular diffusion at the melt interface, while avoiding excessive pressure that could over-compress the thickened adhesive layer. The heat sealing time of 3-5 seconds ensures that heat is fully transferred to all interfaces of the adhesive layer, achieving uniform bonding. Through the synergistic matching of process parameters and the thickened structure, a uniform melt transition zone is formed between the tab adhesive and the aluminum-plastic film.
[0059] Manufacturing process:
[0060] 1. Tab Adhesive Preparation Process: Co-extrusion: Modified PP (60μm), PU (30μm), and PP-g-MAH (30μm) are co-extruded into a composite film using a three-layer co-extrusion casting process. The extrusion temperature is controlled at 230-250℃, the traction speed is 6-8m / min, and the thickness uniformity deviation is ≤±3%. Surface Treatment: The adhesive layer is corona treated to achieve a surface tension ≥42mN / m, ensuring reliable adhesion to the tab metal strip. Temperature control at 230-250℃ ensures that all three materials (modified PP, PU, and PP-g-MAH) reach suitable melt viscosities, guaranteeing similar flow properties during co-extrusion and forming a clear interface and tightly bonded composite structure. The traction speed is set at 6-8 m / min to ensure production efficiency while allowing sufficient cooling and setting time for the adhesive film, ensuring thickness uniformity and dimensional stability. A thickness uniformity deviation of ≤±3% ensures consistent overall thickness of the tab adhesive, providing a stable foundation for subsequent heat-sealing processes and preventing uneven heat-sealing quality due to thickness fluctuations. A surface tension requirement of ≥42 mN / m is achieved by increasing the polarity and roughness of the adhesive layer surface, enhancing the wetting and adhesion performance between the adhesive layer and the tab metal strip. Through optimized co-extrusion process parameters, a composite tab adhesive film with uniform thickness, good interlayer bonding, and excellent surface properties is prepared, providing a high-quality base material for subsequent encapsulation processes.
[0061] 2. Tab Packaging Process: Tab Pretreatment: The surface of the tab metal strip (such as aluminum or nickel strip) is plasma cleaned to remove the oxide layer, with a roughness controlled at 0.8-1.6μm to enhance mechanical adhesion with the adhesive layer. Adhesive Coating and Heat Sealing: A slit coater is used to apply composite tab adhesive to the tab welding end and heat-sealing edge, with a coating width of 5-8mm and a thickness of 0.12mm. After adhesive coating, the tab and aluminum-plastic film are heat-sealed at 180-190℃ and 0.5-0.6MPa for 3-5 seconds to form a sealing area with a width of 10-12mm. The roughness is controlled at 0.8-1.6μm. Plasma cleaning forms a suitable micro-uneven structure on the metal surface, increasing the contact area and mechanical interlocking force between the adhesive layer and the metal surface, while avoiding stress concentration and interface defects caused by excessive roughness. The design of a 5-8mm adhesive coating width and 0.12mm thickness aims to create sufficient adhesive thickness and coverage in the stress-concentrated area at the tab welding end, effectively resisting heat sealing pressure and interfacial stress during charge-discharge cycles. The combination of heat sealing parameters—180-190℃, 0.5-0.6MPa, and 3-5 seconds—is designed to match the thickened adhesive layer structure, ensuring sufficient heat and pressure transfer to the interior of the adhesive layer, resulting in uniform and dense adhesion at all interfaces. The 10-12mm sealing area width ensures sufficient sealing path length, preventing electrolyte leakage even with minor local defects, while avoiding an excessively wide sealing area that could affect the cell's energy density. Through the synergistic optimization of parameters in pretreatment, adhesive coating, and heat sealing processes, a uniform, dense, and reliable sealing structure is formed between the tab and the aluminum-plastic film.
[0062] 3. Performance Verification: Heat Seal Strength Test: A 180° peel test is conducted, requiring a peel force ≥3.8 N / cm, and the failure mode to be cohesive failure of the adhesive layer (rather than interface separation). Cycle Life Test: The packaged cell is cycled at 25°C with a 0.5C charge-discharge cycle, stopping when the capacity drops to 80% of the initial capacity, requiring ≥800 cycles. The requirement of a peel force ≥3.8 N / cm ensures that the heat-sealed interface has sufficient adhesive strength to resist various mechanical and thermal stresses during the use of the cell, preventing electrolyte leakage caused by interface separation, and providing sufficient safety margin for the long-term reliability of the cell. The requirement of ≥800 cycles aims to verify the durability of the tab adhesive structure in long-term charge-discharge cycles, ensuring that the packaging structure can withstand repeated volume changes and stress during cycling. This indicator improves the cycle life by more than 60% compared to the conventional process's 500 cycles. The tab packaging structure of this invention achieves excellent levels in terms of strength, reliability, and durability, providing reliable technical assurance for the safety and long life of the cell.
[0063] Beneficial effects:
[0064] 1. Preventing heat seal breakage: The local thickening design significantly improves the compressive strength of the tab adhesive, enabling it to withstand greater heat sealing pressure, effectively preventing breakage during the heat sealing process, reducing the risk of electrolyte leakage and short circuit, and improving the safety of the battery cell.
[0065] 2. Improved room temperature cycling performance: Through optimized structure and materials, the adhesion to the tabs and aluminum-plastic film is enhanced, reducing detachment and deformation during cycling, thereby improving the room temperature cycling performance of the battery cell. Experimental data shows that after adopting the tab adhesive of this invention, the room temperature cycle life of the pouch cell increases from the conventional 500 cycles to 800 cycles, and the capacity retention rate increases from 80% to 90%.
[0066] 3. Reduced production costs: The localized thickening design of this invention does not require complex production processes and equipment; it can be achieved simply by modifying existing molds, resulting in limited cost increases. Simultaneously, it improves the yield rate of battery cells and reduces the scrap rate due to poor heat sealing, further lowering production costs.
[0067] By adopting the above solution, through localized thickening and a multi-layer composite structure design, the heat-sealing pressure is effectively dispersed, and the bonding strength between the tabs and the aluminum-plastic film is enhanced. This ensures cell safety while further improving the cell's room-temperature cycling performance and extending its lifespan through optimized structure and materials. It also solves the problem of existing soft-pack cell tab adhesives being easily punctured during heat sealing, leading to electrolyte leakage or short circuits.
[0068] In the description of this invention, it should be understood that the terms "coaxial," "bottom," "one end," "top," "middle," "other end," "upper," "side," "top," "inner," "front," "center," "both ends," etc., indicate the orientation or positional relationship based on the orientation or positional relationship shown in the accompanying drawings. They are only for the convenience of describing this invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation. Therefore, they should not be construed as limiting this invention.
[0069] In this invention, unless otherwise explicitly specified and limited, the terms "installation," "setting," "connection," "fixing," "screw connection," etc., should be interpreted broadly. For example, they can refer to a fixed connection, a detachable connection, or an integral part; they can refer to a mechanical connection or an electrical connection; they can refer to a direct connection or an indirect connection through an intermediate medium; they can refer to the internal communication of two components or the interaction between two components. Unless otherwise explicitly limited, those skilled in the art can understand the specific meaning of the above terms in this invention according to the specific circumstances.
[0070] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.
Claims
1. A battery cell electrode packaging structure, characterized in that, have: The tab adhesive consists of a polypropylene base layer, a polyurethane intermediate layer, and an adhesive layer arranged from top to bottom, forming a three-layer structure. The electrode adhesive is applied to the battery cell body and the electrode tabs; The thickness of the tab adhesive located at the tab welding end and heat-sealing edge is greater than the thickness of the tab adhesive at other locations.
2. The electrode packaging structure as described in claim 1, characterized in that, The thickness of the adhesive on the welding end and heat-sealed edge of the electrode tab is 0.12 mm; the thickness of the adhesive on other locations is 0.08 mm.
3. The electrode packaging structure as described in claim 2, characterized in that, The polypropylene base layer is a modified polypropylene with a thickness of 60μm and a melting point of 135-150℃.
4. The electrode packaging structure as described in claim 3, characterized in that, The polyurethane intermediate layer is an elastic polyurethane with a thickness of 30 μm, a glass transition temperature of -40℃, and an elastic modulus ≥12 MPa.
5. The electrode packaging structure as described in claim 4, characterized in that, The adhesive layer is a 30μm thick metalophilic adhesive layer made of maleic anhydride modified polypropylene. It forms a chemical bond with the tab metal strip through polar groups, and the adhesive strength is ≥4.5N / cm.
6. The electrode packaging structure as described in claim 5, characterized in that, The width of the tab adhesive at the welding end of the tab is 5-8mm; the width of the tab adhesive at the heat-sealed edge is 3-5mm.
7. The packaging method for the tab packaging structure as described in any one of claims 1 to 5, characterized in that, Includes the following steps: 1) Preparation of tab adhesive; 2) Use tab adhesive to encapsulate the battery cell; 3) Test the performance of the packaged battery cells.
8. The packaging method for the tab packaging structure as described in claim 7, characterized in that, In step 1) above, modified PP-60μm, PU-30μm, and PP-g-MAH-30μm are used to form a composite film through a three-layer co-extrusion casting process. The extrusion temperature is controlled at 230-250℃, the traction speed is 6-8m / min, and the thickness uniformity deviation is ≤±3%. The adhesive layer is subjected to corona treatment, and the surface tension of the tab metal strip is ≥42mN / m.
9. The packaging method for the tab packaging structure as described in claim 8, characterized in that, In step 2) above, the tab pretreatment is performed by plasma cleaning to remove the oxide layer on the surface of the tab metal strip, and the roughness is controlled at 0.8-1.6μm; adhesive coating and heat sealing are performed by applying composite tab adhesive to the welding end and heat sealing edge of the tab using a slot coater, with a coating width of 5-8mm and a thickness of 0.12mm; after coating, the tab and aluminum-plastic film are heat sealed at 180-190℃ and 0.5-0.6MPa for 3-5 seconds to form a sealing area with a width of 10-12mm.
10. The packaging method for the tab packaging structure as described in claim 9, characterized in that, In step 3) above, the heat seal strength test is performed by conducting a 180° peel test, requiring a peel force ≥3.8N / cm and the failure mode to be cohesive failure of the adhesive layer; the cycle life test is performed by charging and discharging the packaged cell at 0.5C at 25°C until the capacity drops to 80% of the initial capacity, requiring ≥800 cycles.
Citation Information
Patent Citations
Soft package battery cell tab and packaging structure
CN217544868U